Efficacy and safety of 1% forskolin eye drops in open angle glaucoma – An open label study - Majeed, Muhammed (Saudi J Ophthalmol, 2015)
PURPOSE: Current treatment for glaucoma includes beta-blockers and prostaglandin analogues which have their own disadvantages. Thus a need exists for new ocular hypotensive agents that are more efficacious and have fewer side effects. Therefore, forskolin eye drops 1%, through herbal product; a clinical trial was carried out for the safety and efficacy in the treatment of open angle glaucoma. METHODS: Ninety adult male/female patients of 18–60 years of age, of either sex, suffering from open angle glaucoma with an intraocular pressure (IOP) of more than 24 mm Hg were enrolled in the study. Patients were advised to instill 2 drops thrice a day (8:00 h, 14:00 h and 20:00 h) and tonometric readings were recorded on baseline visit and on Visit 2, i.e. end of 1st week, Visit 3–2nd week, Visit 4–3rd week, and Visit 5–4th week. The reduction in IOP across each time point from untreated baseline visit and reduction in IOP across various study visits were measured. RESULTS: The mean (95% CI) difference in reduction in IOP was 4.5 mm Hg (P < 0.05) in the right eye and was 5.4 mm Hg (p < 0.05) in the left eye from baseline visit (Visit 1) to final visit (Visit 5). CONCLUSIONS: Forskolin 1% eye drops can be a safe alternative to beta blockers in glaucoma patients having concomitant asthma.